Increasing day service staff capacity to facilitate positive relationships with people with severe intellectual disability: Evaluation of a new intervention using multiple baseline design. Issue 4 (2nd October 2017) - Johnson, Hilary; Bigby, Christine; Iacono, Teresa; Douglas, Jacinta; Katthagen, Sarah; Bould, Emma
ABSTRACT: Background The social relationships model was developed to describe positive relationships between support staff and people with intellectual disability. We evaluated an educational intervention based on this model. Method Eighteen staff supporting 5 adult service users with severe or profound intellectual disability from 3 day services received the intervention. Mixed methods were used. A multiple baseline design determined changes in relationship processes between staff and service users following intervention. Descriptive field notes and staff interviews provided qualitative data. Results Positive changes in relationship processes were found, but the results were variable. Of note was a high effect for 1 service user, a minimal effect for 2, and no effect for 2 service users. Field notes revealed contributors to variable results, and interview data highlighted changes not captured by quantitative measures. Conclusions An educational intervention based on the social relationship model shows promise as a means to enhance staff relationships with people with intellectual disability.